Multivalent sialylation of beta-thio-glycoclusters by Trypanosoma cruzi trans sialidase and analysis by High Performance Anion Exchange Chromatography - Agusti, Rosalia (2016)
The synthesis of multivalent sialylated glycoclusters is herein addressed by a chemoenzymatic approach using the trans-sialidase of Trypanosoma cruzi (TcTS). Multivalent β-thio-galactopyranosides and β-thio-lactosides were used as acceptor substrates and 3′-sialyllactose as the sialic acid donor. High performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) was shown to be an excellent technique for the analysis of the reaction products. Different eluting conditions were optimized to allow the simultaneous resolution of the sialylated species, as well as their neutral precursors. The TcTS efficiently transferred sialyl residues to di, tri, tetra and octa β-thiogalactosides. In the case of an octavalent thiolactoside, up to six polysialylated compounds could be resolved. Preparative sialylation reactions were performed using the tetravalent and octavalent acceptor substrates. The main sialylated derivatives could be unequivocally assigned by MALDI mass spectrometry. Inhibition of the transfer to the natural substrate, N-acetyllactosamine, was also studied. The octalactoside caused 82 % inhibition of sialic acid transfer when we used equimolar concentrations of donor, acceptor and inhibitor.